Analisis Kelengkapan Dan Keakuratan Pengisian Surgical Safety Checklist Pasien Rawat Inap Bedah Di Rsud Kota Kendari - Dwi Yanti, Suci (Jurnal Kesehatan Mahardika, 2023)
One indicator to assess the quality of  health service in hospital is the availability of complete and accurate medical record (MR). This study aims to determine the level of completeness and accuracy of contents and filling of Surgical safety checklist in the MRs of inpatient surgery in Kendari City Hospital based on PMK number 11 of 2017. The design of this study is quantitative with descriptive approach. This study uses a sampling technique that is simple random sampling. The results of this study are in terms of the completeness of the contents of the Surgical safety checklist which is in the bad category, with a completeness level of less than 100% (95.45%). While in terms of accuracy of filling the Surgical safety checklist is in the category not good that is less than 100% ie (58.42) where this shows weak functioning of the medical record as legal evidence. So, the Hospital needs to hold more routine socialization about SOPs, Director decrees and MR legal regulations to medical officers and Surgical safety checklist.